2009
DOI: 10.1186/1471-2474-10-4
|View full text |Cite
|
Sign up to set email alerts
|

Direction of the formation of anterior lumbar vertebral osteophytes

Abstract: Background: X-ray images of lumbar degenerative diseases often show not only claw osteophytes, but also pairs of osteophytes that form in a direction away from the adjacent disc. We have investigated the direction of the formation of anterior lumbar vertebral osteophytes across the lumbar vertebrae using a sufficient number of lumbar radiographs, because osteophytes images can provide essential information that will contribute to the understanding of the pathology and progress of lumbar spine degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 17 publications
0
28
0
1
Order By: Relevance
“…The lower part of the thoracic spine and the upper part of the lumbar spine are the most frequently involved regions in both conditions (6)(7)(8). Osteophytes, commonly referred to as bone spurs, are bony projections that form along joint margins (9).…”
mentioning
confidence: 99%
“…The lower part of the thoracic spine and the upper part of the lumbar spine are the most frequently involved regions in both conditions (6)(7)(8). Osteophytes, commonly referred to as bone spurs, are bony projections that form along joint margins (9).…”
mentioning
confidence: 99%
“…One study has suggested that bone spurs with an angle of <45° to the anterior vertebral cortex be defined as syndesmophytes, while those with an angle of >45° are defined as degenerative (). However, vertical bone spurs have also been reported in patients with degenerative disorders (). The group considered the 45° angle cutoff as insufficiently supported by the evidence and the consensus was to score bone spurs as syndesmophytes irrespective of the angle unless the bone spur was considered horizontal at the location of a degenerating disc.…”
Section: Resultsmentioning
confidence: 99%
“…Since the original validation of the mSASSS and the pivotal comparative analysis (), there have been further data published on radiographic findings in patients with SpA, healthy individuals, and those with nonspecific spinal disorders (). However, there have been no further studies aimed at standardization and clarification of methodology aimed at enhancing reliability and in assessing the additional value of the anteroposterior (AP) view.…”
Section: Introductionmentioning
confidence: 99%
“…Claw osteophytes are more common at T12 to L2, whilst traction osteophytes (pointing away from the disc) are more common at L3 to L5. Osteophytes were found in 91% of people in an autopsy study …”
Section: Did You Know?mentioning
confidence: 98%
“…The inverse relationship between osteophytes and osteoporosis is well recognised . One study of the spinal X‐rays of postmenopausal women found an inverse relationship between vertebral (osteoporotic) fractures and osteophytes with an odds ratio of 0.38.…”
Section: Did You Know?mentioning
confidence: 99%